The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/s0025315417001308
|View full text |Cite
|
Sign up to set email alerts
|

The use of Fourier analysis as a tool for Oblada melanura (Linnaeus, 1758) stock unit separation in the south central Mediterranean Sea

Abstract: For the first time, an otolith shape analysis was used to investigate the stocks of saddled bream (Oblada melanura, Linnaeus, 1758) in three fishing zones along the Tunisian coast (Bizerte, Kélibia and Sayada). Otolith shape analysis was used on 30 otoliths for each site, sampled during the spawning period. Using elliptic Fourier descriptors (EFD) the quantization of the shape otolith was investigated by SHAPE and multivariate statistical procedures. Considering the environmental and the genotypic aspects, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Other factors can also be considered, such as the life-history traits associated with the otolith shape (Mérigot et al, 2007) and biological and behavioural characteristics, such as the type of swimming activity (Lord et al, 2012). This effect of environmental factors on the shape of otolith in Tunisian waters has also been previously recognized in P. erythrinus (Mejri et al, 2018), D. annularis (Trojette et al, 2015) and O. melanura (Barhoumi et al, 2018). Previous studies on the size and morphology of the otoliths have shown that the intra-population variation may reside in inter-and intra-individual and even inter-population variations (Mejri et al, 2018(Mejri et al, , 2020.…”
Section: Discussionmentioning
confidence: 85%
“…Other factors can also be considered, such as the life-history traits associated with the otolith shape (Mérigot et al, 2007) and biological and behavioural characteristics, such as the type of swimming activity (Lord et al, 2012). This effect of environmental factors on the shape of otolith in Tunisian waters has also been previously recognized in P. erythrinus (Mejri et al, 2018), D. annularis (Trojette et al, 2015) and O. melanura (Barhoumi et al, 2018). Previous studies on the size and morphology of the otoliths have shown that the intra-population variation may reside in inter-and intra-individual and even inter-population variations (Mejri et al, 2018(Mejri et al, , 2020.…”
Section: Discussionmentioning
confidence: 85%
“…Similar results have previously been reported in a range of sparids, including D . annularis (Trojette et al ., 2015), Oblada melanura (Barhoumi et al ., 2018), Pagellus erythrinus (Mejri et al ., 2020) and B . boops (Ider et al ., 2017; Ben Labidi et al ., 2020 a ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cage-reared L. maculatus have been imported from China into Korea and Japan for human consumption (An et al 2014). Germplasm degradation and a reduction in disease resistance of cultured L. maculatus restricts its sustainable development (Wang et al 2017), and calls for an assessment of the population structure of this fish (Barhoumi et al 2017). The results of such study can be used to prevent overfishing and ultimately declines in the numbers of L. maculatus.…”
Section: Introductionmentioning
confidence: 99%